Modeling Unsteady Flow Characteristics of Hydropeaking Operations and Their Implications on Fish Habitat - Shen, Yi; Diplas, Panayiotis (Journal of hydraulic engineering (New York, N.Y.), 2010)
Reservoir releases associated with energy production and flood mitigation need to be reconciled with efforts to maintain healthy ecosystems in regulated rivers. Unsteady flow phenomena caused by hydropeaking operations typically affect riverbed erosion and fish displacement. A three-dimensional hydrodynamic model is used to simulate the flow characteristics during the passage of the rising limb of an observed hydropeaking event in a gravel-bed reach of Smith River, Virginia. The calculated time-dependent water surface elevations, velocities, and shear stresses are compared with field measurements. Further, comparison based on numerical simulations of this historical and a hypothetical “staggering” hydropeaking event reveals that the latter has the capability of reducing the area subject to erosion and prolonging refugia availability for juvenile brown trout. Issues related to the adoption of either a truly dynamic modeling approach or a quasi-steady methodology for simulating unsteady flows are examined through a proposed unsteadiness flow parameter. The insights obtained from this study can assist in properly accounting for the impact of hydropeaking operations on fish habitat and instream flow management.